An Immunoregulatory Role of Interleukin-3 in Allergic Asthma - Krammer, Susanne; Yang, Zuqin; Zimmermann, Theodor; Xepapadaki, Paraskevi; Geppert, Carol-Immanuel; Papadopoulos, Nikolaos G.; Finotto, Susetta (Frontiers in Immunology, 2022)
Background: Allergic asthma is a chronic airway inflammatory disease associated with airway mucus hyper-production. ILC2 cells, which express the Th2 transcription factor GATA3, have been associated with allergic asthma. The cytokine IL-3 is known to support eosinophil, basophil and mucosal mast cell differentiation and survival; however, its role on T regulatory cells as well as on lung ILC2 and in pediatric asthma needs further investigation. Objectives: To investigate the role of IL-3 in preschool children and to explore its therapeutic role in experimental asthma. Methods: In a cohort of preschool children with and without asthma, we analyzed the secretion of IL-3 in nasopharyngeal fluid (NPF) and IL-3 receptor (R) alpha chain mRNA expression in peripheral blood mononuclear cells (PBMCs). In a murine model of allergic asthma, we analyzed the phenotype of wild-type untreated and rIL-3 intranasally treated asthmatic mice. Results: IL-3 was found downregulated in the nasopharyngeal fluid of children with partially controlled asthma, as compared to control children. Moreover, IL-3 was found induced in phytohemagglutinin (PHA)-stimulated PBMCs from children with asthma and treated with steroids. Finally, IL-3 in NPF directly correlated with the anti-inflammatory molecule sST2 in steroid-treated asthmatic children. Intranasal rIL-3 delivery in vivo during the challenge phase decreased airway mucus production and inflammatory eosinophils. Moreover, rIL-3 given during the challenge phase, reduced lung ST2intGATA3+ILC2, accompanied by an induction of T regulatory cells in the airways. Conclusions: IL-3 was found associated with steroid-resolved asthma. Moreover, treatment with rIL-3 resulted in amelioration of airway eosinophilia and mucus production, two main pathophysiological conditions associated with asthma in a murine model of allergic asthma. Thus, rIL-3 opens new strategies for immunotherapy of this disease.
CRIS-Team Scopus Importer:2022-03-25
Keywords: allergic asthma; eosinophils; IL-3; ILC2s; T regulatory cells

Clinical correlates of rhinovirus infection in preschool asthma - Jartti, Tuomas; Liimatainen, Unna; Xepapadaki, Paraskevi; Vahlberg, Tero; Bachert, Claus; Finotto, Susetta; Kowalski, Marek L.; Sobanska, Anna; Lukkarinen, Heikki; Pasioti, Maria; Vuorinen, Tytti; Zhang, Nan; et al. (Allergy, 2020)
Background: Investigation of preschool asthma is important since not all children outgrow their illness during this age. Data are scarce on the role of rhinovirus (RV) infections in this patient group. Objectives: To investigate the role of RV infections in preschool asthma: (i) susceptibility factors, (ii) clinical course, and (iii) medium-term outcome. Methods: A total of 130 asthmatic children aged 4-6 years from the multinational PreDicta cohort were prospectively followed for a 12-month period. Allergy tests and a standard health questionnaire were carried out at study entry. Respiratory virus presence in nasopharyngeal washes was studied at illness visits and at 3 scheduled visits. Results: At study entry, mean age of the children was 5.3 years. Of 571 visits, 54% were positive for any virus and 39% for RV. Patient characteristics were only assessed with RV infection due to low number of other viruses. The use of supplementary vitamin D was inversely associated with RV infection (P <.05). RV infection was associated with more severe course of acute illness in terms of more severe nighttime coughing, more sleep disturbances, and more days with runny nose (all P <.05). RV infection was also associated with more severe disease course during the 12-month follow-up in terms of more nights with awakenings and more days of exercise-related symptoms (both P <.05). Conclusions: Vitamin D supplementation may have an anti-rhinovirus effect. Both short- and medium-term outcomes suggest RV infection to be an important clinical marker of instable preschool asthma.
CRIS-Team Scopus Importer:2020-07-31
Keywords: asthma; child; preschool; rhinovirus; vitamin D

Contribution of repeated infections in asthma persistence from preschool to school age: Design and characteristics of the PreDicta cohort - Xepapadaki, Paraskevi; Bachert, Claus; Finotto, Susetta; Jartti, Tuomas; Konstantinou, George N.; Kiefer, Alexander; Kowalski, Marek; Lewandowska-Polak, Anna; Lukkarinen, Heikki; Roumpedaki, Eirini; Sobanska, Anna; Sintobin, Ina; et al. (Pediatric Allergy and Immunology, 2018)
BACKGROUND: The PreDicta cohort was designed to prospectively evaluate wheeze/asthma persistence in preschoolers in association with viral/microbial exposures and immunological responses. We present the cohort design and demographic/disease characteristics and evaluate unsupervised and predefined phenotypic subgroups at inclusion. METHODS: PreDicta is a 2-year prospective study conducted in five European regions, including children 4-6 years with a diagnosis of asthma as cases and healthy age-matched controls. At baseline, detailed information on demographics, asthma and allergy-related disease activity, exposures, and lifestyle were recorded. Lung function, airway inflammation, and immune responses were also assessed. Power analysis confirmed that the cohort is adequate to answer the initial hypothesis. RESULTS: A total of 167 asthmatic children (102 males) and 66 healthy controls (30 males) were included. Groups were homogeneous in respect to most baseline characteristics, with the exception of male gender in cases (61%) and exposure to tobacco smoke. Comorbidities and number and duration of infections were significantly higher in asthmatics than controls. 55.7% of asthmatic children had at least one positive skin prick test to aeroallergens (controls: 33.3%, P = .002). Spirometric and exhaled nitric oxide values were within normal limits; only baseline FEV0.5 and FEV1 reversibility values were significantly different between groups. Viral infections were the most common triggers (89.2%) independent of severity, control, or atopy; however, overlapping phenotypes were also common. Severity and control clustered together in an unsupervised analysis, separating moderate from mild disease. CONCLUSIONS: The PreDicta cohort presented no differences in non-asthma related measures; however, it is well balanced regarding key phenotypic characteristics representative of "preschool asthma".
EVALuna2:52975

CTLA4 induction by Rhinovirus (RV) in pediatric asthma - Kölle, Julia; Haag, Patricia; Vuorinen, T.; Kiefer, Alexander; Zimmermann, Theodor; Papadopoulos, N. G.; Finotto, Susetta (2018)
EVALuna2:34821

Evolution of airway inflammation in preschoolers with asthma-results of a two-year longitudinal study - Xepapadaki, P.; Korovessi, P.; Bachert, C.; Finotto, Susetta; Jartti, T.; Lakoumentas, J.; Kowalski, M. L.; Lewandowska-Polak, A.; Lukkarinen, H.; Zhang, N.; Zimmermann, Theodor; Papadopoulos, N. G. (ALLERGY, 2020)
CRIS-Team WoS Importer:2020-10-02

Evolution of Airway Inflammation in Preschoolers with Asthma-Results of a Two-Year Longitudinal Study - Xepapadaki, Paraskevi; Korovessi, Paraskevi; Bachert, Claus; Neurath-Finotto, Susetta; Jartti, Tuomas; Lakoumentas, John; Kowalski, Marek L.; Lewandowska-Polak, Anna; Lukkarinen, Heikki; Zhang, Nan; Zimmermann, Theodor; Papadopoulos, Nikolaos G. (Journal of Clinical Medicine, 2020)
Fractional exhaled nitric oxide (FeNO) is a non-invasive marker for eosinophilic airway inflammation and has been used for monitoring asthma. Here, we assess the characteristics of FeNO from preschool to school age, in parallel with asthma activity. A total of 167 asthmatic children and 66 healthy, age-matched controls were included in the 2-year prospective PreDicta study evaluating wheeze/asthma persistence in preschool-aged children. Information on asthma/rhinitis activity, infections and atopy was recorded at baseline. Follow-up visits were performed at 6-month intervals, as well as upon exacerbation/cold and 4-6 weeks later in the asthmatic group. We obtained 539 FeNO measurements from asthmatics and 42 from controls. At baseline, FeNO values did not differ between the two groups (median: 3.0 ppb vs. 2.0 ppb, respectively). FeNO values at 6, 12, 18 and 24 months (4.0, CI: 0.0-8.6; 6.0, CI: 2.8-12.0; 8.0, CI: 4.0-14.0; 8.5, CI: 4.4-14.5 ppb, respectively) increased with age (correlation p ≤ 0.001) and atopy (p = 0.03). FeNO was non-significantly increased from baseline to the symptomatic visit, while it decreased after convalescence (p = 0.007). Markers of disease activity, such as wheezing episodes and days with asthma were associated with increased FeNO values during the study (p < 0.05 for all). Age, atopy and disease activity were found to be important FeNO determinants in preschool children. Longitudinal and individualized FeNO assessment may be valuable in monitoring asthmatic children with recurrent wheezing or mild asthma.
EVALuna2:211404

IFN-α/IFN-λ responses to respiratory viruses in paediatric asthma - Bergauer, Annika; Sopel, Nina; Kross, Bettina; Vuorinen, Tytti; Xepapadaki, Paraskevi; Weiss, Scott T.; Blau, Ashley; Sharma, Himanshu; Kraus, Cornelia; Springel, Rebekka; Rauh, Manfred; Mittler, Susanne; et al. (European Respiratory Journal, 2016)
We analysed the influence of rhinovirus (RV) in nasopharyngeal fluid (NPF) on type I and III interferon (IFN) responses (e.g. IFN-? and IFN -: ?) and their signal transduction, at baseline and during disease exacerbation, in cohorts of pre-school children with and without asthma.At the time of recruitment into the Europe-wide study PreDicta, and during symptoms, NPF was collected and the local RV colonisation was analysed. Peripheral blood mononuclear cells (PBMCs) were challenged in vitro with RV or not. RNA was analysed by quantitative real-time PCR and gene arrays. Serum was analysed with ELISA for IFNs and C-reactive protein.We found that PBMCs from asthmatic children infected in vitro with the RV1b serotype upregulated MYD88, IRF1, STAT1 and STAT2 mRNA, whereas MYD88, IRF1, STAT1 and IRF9 were predominantly induced in control children. Moreover, during symptomatic visits because of disease exacerbation associated with RV detection in NPF, IFN-? production was found increased, while IFN-? secretion was already induced by RV in asthmatic children at baseline.During asthma exacerbations associated with RV, asthmatic children can induce IFN-? secretion, indicating a hyperactive immune response to repeated respiratory virus infection.
EVALuna2:9365

IFN-α/IFN-λ responses to respiratory viruses in paediatric asthma - Bergauer, Annika; Sopel, Nina; Kross, Bettina; Vuorinen, Tytti; Xepapadaki, Paraskevi; Weiss, Scott T.; Blau, Ashley; Sharma, Himanshu; Kraus, Cornelia; Springel, Rebekka; Rauh, Manfred; Mittler, Susanne; et al. (European Respiratory Journal, 2017)
EVALuna:34061

IL-33/ST2 immune responses to respiratory bacteria in pediatric asthma - Hentschke, Isabell; Graser, Anna; Melichar, Volker O.; Kiefer, Alexander; Zimmermann, Theodor; Kross, Bettina; Haag, Patricia; Xepapadaki, Paraskevi; Papadopoulos, Nikolaos G.; Bogdan, Christian; Finotto, Susetta (Scientific Reports, 2017)
Here we investigated the relationship between local bacterial colonization and anti-bacterial immune responses in pre-school asthmatic and control children within the EU-wide study PreDicta. In this cohort of pre-school asthmatic children, nasopharyngeal colonization with Gram-negative bacteria such as Haemophilus influenzae and Moraxella catarrhalis was found to be associated with the highest interferon beta (IFN?) and IL-33 levels in the nasal pharyngeal fluids (NPF). IL33R-ST2 was found induced in the blood of asthmatic children with additional Gram + bacteria in the nasopharynx (Gr+/-). Furthermore, asthmatic children had more episodes of infection that required antibiotic therapy than the control group. Treatment with antibiotics associated with reduced ST2 in blood cells of both asthmatic and control children and reduced IL-33 levels in the airways of asthmatic children. In the absence of Staphylococcus (S.) aureus in NPF, antibiotic therapy associated with decreased IL-33 levels in the NPF and lower ST2 values in the blood of control children but not of asthmatic children. These data suggest that, in asthmatic children, Gram- bacteria, which persist after antibiotic therapy, contributes to IL-33 locally and associated with Gr + bacteria colonization in the airways, inhibited IFN-? and in the absence of Staphylococcus (S.) aureus, induced ST2 bearing cells in their blood.
EVALuna2:7728

IL-6 activated integrated BATF/IRF4 functions in lymphocytes are T-bet-independent and reversed by subcutaneous immunotherapy - Mousset, Stephanie; Koch, Sonja; Mousset, Stephanie; Graser, Anna; Reppert, Sarah; Uebel, Caroline; Reinhardt, Cornelia; Zimmermann, Theodor; Rieker, Ralf; Lehr, Hans A.; Finotto, Susetta (Scientific Reports, 2013)
IL-6 plays a central role in supporting pathological TH2 and TH17 cell development and inhibiting the protective T regulatory cells in allergic asthma. TH17 cells have been demonstrated to regulate allergic asthma in general and T-bet-deficiency-induced asthma in particular. Here we found an inverse correlation between T-bet and Il-6 mRNA expression in asthmatic children. Moreover, experimental subcutaneous immunotherapy (SIT) in T-bet((-/-)) mice inhibited IL-6, IL-21R and lung TH17 cells in a setting of asthma. Finally, local delivery of an anti-IL-6R antibody in T-bet((-/-)) mice resulted in the resolution of this allergic trait. Noteworthy, BATF, crucial for the immunoglobulin-class-switch and TH2,TH17 development, was found down-regulated in the lungs of T-bet((-/-)) mice after SIT and after treatment with anti-IL-6R antibody, indicating a critical role of IL-6 in controlling BATF/IRF4 integrated functions in TH2, TH17 cells and B cells also in a T-bet independent fashion in allergic asthma.

Immunoregulatory role of NFAT-interacting protein (NIP) 45 in adaptive and innate immune responses in allergic asthma - Koch, Sonja; Maeding, N.; Karwot, R.; Mirzakhani, H.; Springel, R.; Mittler, S.; Zimmermann, Theodor; Melichar, V. O.; Knipfer, Lisa; Wirtz, Stefan; Weiss, S. T. (2017)
EVALuna2:33897

Increased expression of nuclear factor of activated T cells 1 drives IL-9-mediated allergic asthma - Koch, Sonja; Graser, Anna; Mirzakhani, Hooman; Zimmermann, Theodor; Melichar, Volker O.; Woelfel, Marco; Croteau-Chonka, Damien C.; Raby, Benjamin A.; Weiss, Scott T.; Finotto, Susetta (Journal of Allergy and Clinical Immunology, 2016)
EVALuna2:25981

Regulated on Activation, Normal T cell Expressed and Secreted (RANTES) drives the resolution of allergic asthma - Li, Nina; Mirzakhani, Hoomann; Kiefer, Alexander; Kölle, Julia; Vuorinen, Tytti; Rauh, Manfred; Yang, Zuqin; Krammer, Susanne; Xepapadaki, Paraskevi; Lewandowska-Polak, Anna; Lukkarinen, Heikki; Zhang, Nan; et al. (iScience, 2021)
RANTES is implicated in allergic asthma and in T cell-dependent clearance of infection. RANTES receptor family comprises CCR1, CCR3, and CCR5, which are G-protein-coupled receptors consisting of seven transmembrane helices. Infections with respiratory viruses like Rhinovirus cause induction of RANTES production by epithelial cells. Here, we studied the role of RANTES in the peripheral blood mononuclear cells in cohorts of children with and without asthma and validated and extended this study to the airways of adults with and without asthma. We further translated these studies to a murine model of asthma induced by house dust mite allergen in wild-type RANTES and CCR5-deficient mice. Here we show an unpredicted therapeutic role of RANTES in the resolution of allergen-induced asthma by orchestrating the transition of effector GATA-3+CD4+ T cells into immune-regulatory-type T cells and inflammatory eosinophils into resident eosinophils as well as increased IL-10 production in the lung.
CRIS-Team WoS Importer:2021-11-19

Respiratory infections regulated blood cells IFN-β-PD-L1 pathway in pediatric asthma - Kölle, Julia; Haag, Patricia; Vuorinen, Tytti; Kiefer, Alexander; Rauh, Manfred; Zimmermann, Theodor; Papadopoulos, Nikolaos G.; Finotto, Susetta (Immunity, Inflammation and Disease, 2020)
Background: Respiratory infections, in general, and rhinovirus infection specifically are the main reason for asthma exacerbation in children and programmed cell death protein 1 ligand (PD-L1) expression inhibits T cell responses. Objective: Could the interferon (IFN) type I expression in peripheral blood mononuclear cells (PBMCs) improve disease exacerbation in pediatric asthma?. Results: Here we found increased level of PD-L1 messenger RNA (mRNA) in total blood cells isolated from preschool children with virus-induced asthma, with lower percentage of forced expiratory volume in 1 second and with high serum levels of the C-reactive-protein. Conclusions and Clinical Relevance: These data indicate that, in the presence of infection in the airways of preschool children, worse asthma is associated with induced PD-L1 mRNA expression in blood cells. Further, type I IFN, IFN-β, a cytokine that is involved in the clearance of infections, was found to be associated with a better lung function in asthmatic children. These data suggest that improving peripheral blood IFN type I expression in PBMCs in pediatric asthma could improve disease exacerbation due to suppressing PD-L1 expression in blood cells.
CRIS-Team Scopus Importer:2020-05-22
Keywords: human rhinovirus; IFNβ; PD-L1; pediatric asthma

Rhinovirus inhibits IL-17A and the downstream immune responses in allergic asthma - Graser, Anna; Ekici, Arif Bülent; Sopel, Nina; Melichar, V. O.; Zimmermann, Theodor; Papadopoulos, N. G.; Taka, S.; Ferrazzi, Fulvia; Vuorinen, T.; Finotto, Susetta (Mucosal Immunology, 2016)
The proinflammatory cytokine interleukin-17A (IL-17A) is known to mediate antimicrobial activity, but its role during rhinovirus (RV) infections and in asthma needs further investigation. Therefore, we addressed the role of IL-17A during allergic asthma and antiviral immune response in human and murine immunocompetent cells. In this study we found that asthmatic children with a RV infection in their upper airways have upregulated mRNA levels of the antiviral cytokine interferon type I (IFN)-? and the transcription factor T-box 21 (TBX21) and reduced levels of IL-17A protein in their peripheral blood mononuclear cells (PBMCs). We also found that IL-17A inhibited RV1b replication in infected human lung epithelial cells A549. Furthermore, by using gene array analysis we discovered that targeted deletion of Il17a in murine lung CD4(+) T cells impaired Oas1g mRNA downstream of Ifn?, independently from RV infection. Additionally, in PBMCs of children with a RV infection in their nasalpharyngeal fluid OAS1 gene expression was found downregulated. Finally RV1b inhibited IL-17A production in lung CD4(+) T cells in a setting of experimental asthma. These results indicate that the RV1b inhibits IL-17A in T helper type 17 cells and IL-17A clears RV1b infection in epithelial cells. In both cases IL-17A contributes to fend off RV1b infection by inducing genes downstream of interferon type I pathway.
EVALuna2:9312

Rhinovirus species/genotypes and interferon-λ: subtypes, receptor and polymorphisms - missing pieces of the puzzle of childhood asthma? - Bergauer, Annika; Sopel, Nina; Kro, Bettina; Vuorinen, Tytti; Xepapadaki, Paraskevi; Weiss, Scott T.; Blau, Ashley; Sharma, Himanshu; Kraus, Cornelia; Springel, Rebekka; Rauh, Manfred; Mittler, Susanne; et al. (European Respiratory Journal, 2017)
EVALuna2:25986

Rhinovirus Species-Specific Antibodies Differentially Reflect Clinical Outcomes in Health and Asthma - Megremis, Spyridon; Niespodziana, Katarzyna; Cabauatan, Clarissa; Xepapadaki, Paraskevi; Kowalski, Marek L.; Jartti, Tuomas; Bachert, Claus; Finotto, Susetta; West, Peter; Stamataki, Sofia; Lewandowska-Polak, Anna; Lukkarinen, Heikki; et al. (American Journal of Respiratory and Critical Care Medicine, 2018)
RATIONALE: Rhinoviruses are major triggers of common cold and acute asthma exacerbations; Rhinovirus species A, B and C may have distinct clinical impact; however, little is known regarding RV species-specific antibody responses in health and asthma. OBJECTIVES: To describe and compare total and rhinovirus species-specific antibody levels in healthy and asthmatic children, away from an acute event. METHODS: Serum samples from 163 preschool children with mild to moderate asthma and 72 healthy controls from the multinational Predicta cohort were analysed using the recently developed PreDicta rhinovirus antibody chip. MAIN RESULTS: Rhinovirus antibody levels varied, with rhinovirus C and rhinovirus A being higher than rhinovirus B in both groups. Compared to controls, asthma was characterised by significantly higher levels of antibodies to rhinovirus A and rhinovirus C, but not rhinovirus B. Rhinovirus antibody levels positively correlated with the number of common colds over the previous year in healthy children, and wheeze episodes in asthmatics. Antibody levels also positively correlated with asthma severity but not with current asthma control. CONCLUSIONS: The variable humoral response to rhinovirus species in both groups, suggests a differential infectivity pattern between rhinovirus species. In healthy pre-schoolers, rhinovirus antibodies accumulate with colds. In asthma, rhinovirus A and rhinovirus C antibodies are much higher and further increase with disease severity and wheeze episodes. Higher antibody levels in asthma may be due to a compromised innate immune response, leading to increased exposure of the adaptive immunity to the virus. Importantly, there is no apparent protection with increasing levels of antibodies.
EVALuna2:52974

Risk factors for complicated lymphadenitis caused by nontuberculous mycobacteria in children - Kuntz, Martin; Kohlfürst, Daniela S.; Feiterna-Sperling, Cornelia; Krüger, Renate; Baumann, Ulrich; Buchtala, Laura; Elling, Roland; Grote, Veit; Hübner, Johannes; Hufnagel, Markus; Kaiser-Labusch, Petra; Liese, Johannes; et al. (Emerging Infectious Diseases, 2020)
Nontuberculous mycobacteria (NTM) are an emerging cause of infections, including chronic lymphadenitis in children. To identify risk factors for NTM lymphadenitis, particularly complicated disease, we collected epidemiologic, clinical, and microbiological data on 138 cases of NTM lymphadenitis in children across 13 centers in Germany and Austria. We assessed lifestyle factors but did not identify specific risk behaviors. We noted that more cases of NTM lymphadenitis occurred during cold months than during warm months. Moreover, we noted female sex and age <5.5 years as potential risk factors. Complete extirpation of the affected lymph node appeared to be the best therapeutic measure. We integrated the study data to develop a simple risk score to predict unfavorable clinical outcomes for NTM lymphadenitis.
CRIS-Team Scopus Importer:2020-04-03

Role of nuclear factor of activated T cells 2 (NFATc2) in allergic asthma - Jakobi, M.; Mirzakahni, H.; Kiefer, Alexander; Rauh, Manfred; Zimmermann, Theodor; Papadopoulos, N. G.; Raby, B. A.; Weiss, S. T.; Finotto, Susetta (ALLERGY, 2020)
CRIS-Team WoS Importer:2020-10-02

Role of TGF-β in anti-rhinovirus immune responses in asthmatic patients - Bielor, Carina; Sopel, Nina; Maier, Anja; Blau, Ashley; Sharma, Himanshu; Vuorinen, Tytti; Kross, Bettina; Mittler, Susanne; Graser, Anna; Mousset, Stephanie; Melichar, Volker O.; Kiefer, Alexander; et al. (Journal of Allergy and Clinical Immunology, 2017)
EVALuna2:32796

Severity of asthma symptoms, lung function and airway inflammation in the PreDicta cohort of preschool-age children with asthma - Roumpedaki, E.; Karantoumanis, D.; Xepapadaki, P.; Sintobin; Bachert, C.; Lukkarinen, H.; Jartti, T.; Zimmermann, Theodor; Finotto, Susetta; Sobanska, Anna; Kowalski, M.; Papadopoulos, N. G. (2015)
EVALuna2:33298

Soluble ST2 regulation by rhinovirus and 25(OH)-vitamin D3 in the blood of asthmatic children - Haag, Patricia; Sharma, H.; Rauh, Manfred; Zimmermann, Theodor; Vuorinen, T.; Papadopoulos, N. G.; Weiss, S. T.; Finotto, Susetta (Clinical and Experimental Immunology, 2018)
Paediatric asthma exacerbations are often caused by rhinovirus (RV). Moreover, 25(OH)-vitamin D3 (VitD3) deficiency during infancy was found associated with asthma. Here, we investigated the innate immune responses to RV and their possible modulation by 25(OH)-VitD3 serum levels in a preschool cohort of children with and without asthma. The innate lymphoid cell type 2 (ILC2)-associated marker, ST2, was found up-regulated in the blood cells of asthmatic children with low serum levels of 25(OH)-VitD3 in the absence of RV in their airways. Furthermore, in blood cells from control and asthmatic children with RV in their airways, soluble (s) ST2 (sST2) protein was found reduced. Asthmatic children with low 25(OH)-VitD3 in serum and with RV in vivo in their airways at the time of the analysis had the lowest sST2 protein levels in the peripheral blood compared to control children without RV and high levels of 25(OH)-VitD3. Amphiregulin (AREG), another ILC2-associated marker, was found induced in the control children with RV in their airways and low serum levels of 25(OH)-VitD3. In conclusion, the anti-inflammatory soluble form of ST2, also known as sST2, in serum correlated directly with interleukin (IL)-33 in the airways of asthmatic children. Furthermore, RV colonization in the airways and low serum levels of 25(OH)-VitD3 were found to be associated with down-regulation of sST2 in serum in paediatric asthma. These data indicate a counter-regulatory role of 25(OH)-VitD3 on RV-induced down-regulation of serum sST2 in paediatric asthma, which is relevant for the therapy of this disease.
EVALuna2:35820

Targeted deletion of Interleukin-3 results in asthma exacerbations - Kölle, Julia; Zimmermann, Theodor; Kiefer, Alexander; Rieker, Ralf; Xepapadaki, Paraskevi; Zundler, Sebastian; Papadopoulos, Nikolaos G.; Finotto, Susetta (iScience, 2022)
The cytokine interleukin-3 (IL-3) acts on early hematopoietic precursor cells. In humans, Treg cells secrete IL-3 and repress inflammatory cells except for basophils. The present study aims to elucidate the contribution of IL-3 in the development and the course of allergic asthma. We therefore analyzed the secretion of IL-3 in PBMCs and total blood cells in two cohorts of pre-school children with and without asthma. In a murine model of allergic asthma, we analyzed the phenotype of IL-3−/− mice compared to wild-type mice. PBMCs from asthmatic children showed increased IL-3 secretion, which directly correlated with improved lung function. IL-3−/− asthmatic mice showed increased asthmatic traits. Moreover, IL-3-deficient mice had a defect in T regulatory cells in the lung. In conclusion, IL-3 downregulation was found associated with more severe allergic asthma in pre-school children. Consistently, targeting IL-3 resulted in an induced pathophysiological response in a murine model of allergic asthma.
CRIS-Team Scopus Importer:2022-07-15
Keywords: Biological sciences; immune response; Immunology

Targeted deletion of NFAT-Interacting-Protein-(NIP) 45 resolves experimental asthma by inhibiting Innate Lymphoid Cells group 2 (ILC2) - Koch, Sonja; Knipfer, Lisa; Kölle, Julia; Mirzakhani, Hooman; Graser, Anna; Zimmermann, Theodor; Kiefer, Alexander; Melichar, Volker O.; Rascher, Wolfgang; Papadopoulos, Nikolaos G.; Rieker, Ralf; Raby, Benjamin A.; et al. (Scientific Reports, 2019)
Here we investigated the role of NFAT-interacting protein (NIP)-45, an Interleukin (IL)-4 inducing Transcription Factor, and its impact on the differentiation of Group 2 Innate -Lymphoid -Cells (ILC2s) in the pathogenesis of asthma. NIP45, a transcription factor regulating NFATc1 activity, mRNA was found to be induced in the Peripheral Blood mononuclear cells (PMBCs) of asthmatic pre-school children with allergies and in the peripheral blood CD4+ T cells from adult asthmatic patients. In PBMCs of asthmatic and control children, NIP45 mRNA directly correlated with NFATc1 but not with T-bet. Targeted deletion of NIP45 in mice resulted in a protective phenotype in experimental asthma with reduced airway mucus production, airway hyperresponsiveness and eosinophils. This phenotype was reversed by intranasal delivery of recombinant r-IL-33. Consistently, ILC2s and not GATA3+ CD4+ T-cells were decreased in the lungs of asthmatic NIP45−/− mice. Reduced cell number spleen ILC2s could be differentiated from NIP45−/− as compared to wild-type mice after in vivo injection of a microcircle-DNA vector expressing IL-25 and decreased cytokines and ILC2 markers in ILC2 differentiated from the bone marrow of NIP45−/− mice. NIP45 thus emerges as a new therapeutic target for the resolution of the airway pathology, down-regulation of ILC2s and mucus production in asthma.
CRIS-Team Scopus Importer:2019-11-08

Tgf-beta regulation and regulated anti-rhinovirus (RV) immune responses in asthma - Finotto, Susetta; Bielor, Carina; Sopel, Nina; Vuorinen, T.; Melichar, V. O.; Kiefer, Alexander; Zimmermann, Theodor; Papadopoulos, N. G.; Weiss, S. T. (2017)
EVALuna2:33023

The activating protein 1 transcription factor basic leucine zipper transcription factor, ATF-like (BATF), regulates lymphocyte- and mast cell-driven immune responses in the setting of allergic asthma - Ubel, Caroline; Sopel, Nina; Graser, Anna; Hildner, Kai; Reinhardt, Cornelia; Zimmermann, Theodor; Rieker, Ralf Joachim; Maier, Anja; Neurath, Markus; Murphy, Kenneth M.; Finotto, Susetta (Journal of Allergy and Clinical Immunology, 2014)
Mice without the basic leucine zipper transcription factor, ATF-like (BATF) gene (Batf(-/-)) lack TH17 and follicular helper T cells, which demonstrates that Batf is a transcription factor important for T- and B-cell differentiation.In this study we examined whether BATF expression would influence allergic asthma.In a cohort of preschool control children and children with asthma, we analyzed BATF mRNA expression using real-time PCR in PBMCs. In a murine model of allergic asthma, we analyzed differences in this allergic disease between wild-type, Batf transgenic, and Batf(-/-) mice.In the absence of corticosteroid treatment, children with recurrent asthma have a significant increase in BATF mRNA expression in their PBMCs. Batf(-/-) mice display a significant reduction in the pathophysiologic responses seen in asthmatic wild-type littermates. Moreover, we discovered a decrease in IL-3 production and IL-3-dependent mast cell development in Batf(-/-) mice. By contrast, IFN-? was induced in lung CD4(+) and CD8(+) T cells. Intranasal delivery of anti-IFN-? antibodies induced airway hyperresponsiveness and inflammation in wild-type but not in Batf(-/-) mice. Transgenic overexpression of Batf under the control of the CD2 promoter/enhancer augmented lung inflammation and IgE levels in the setting of experimental asthma.BATF is increased in non-steroid-treated asthmatic children. Targeting BATF expression resulted in amelioration of the pathophysiologic responses seen in children with allergic asthma, and BATF has emerged as a novel target for antiasthma interventions.
EVALuna2:1742

The anti-viral properties of IL-17A in allergic asthma - Graser, Anna; Ekici, Arif Bülent; Melichar, Volker O.; Zimmermann, Theodor; Papadopoulos, Nikolaos G.; Taka, Stella; Ferrazzi, Fulvia; Vuorinen, Tytti; Finotto, Susetta (2015)
EVALuna2:25975

The role of interferon type I and type III receptors in rhinovirus induced allergic asthma - Krug, J.; Kölle, Julia; Kiefer, Alexander; Vuorinen, T.; Xepapadaki, P.; Stanic, B.; Akdis, M.; Zimmermann, Theodor; Papadopoulos, N. G.; Finotto, Susetta; Chiriac, Mircea-Teodor (ALLERGY, 2020)
CRIS-Team WoS Importer:2020-10-02

The role of interleukin 3 (IL3) in allergic asthma - Kölle, Julia; Vuorinen, T.; Kiefer, Alexander; Zimmermann, Theodor; Xepapadaki, P.; Rieker, Ralf; Papadopoulos, N. G.; Finotto, Susetta (ALLERGY, 2020)
CRIS-Team WoS Importer:2020-10-02

The role of regulated on activation, normal T cell expressed and secreted (RANTES) in allergic asthma - Li, N.; Kölle, Julia; Kiefer, Alexander; Xepapadaki, P.; Kowalski, M. L.; Bachert, C.; Jartti, T.; Vuorinen, T.; Lewandowska-Polak, A.; Zhang, N.; Lukkarinen, H.; Zimmermann, Theodor; et al. (ALLERGY, 2020)
CRIS-Team WoS Importer:2020-10-02

TLR7/8 regulates type I and type III interferon signalling in rhinovirus 1b-induced allergic asthma - Krug, Jasmin; Kiefer, Alexander; Kölle, Julia; Vuorinen, Tytti; Xepapadaki, Paraskevi; Stanic, Barbara; Chiriac, Mircea-Teodor; Akdis, Muebeccel; Zimmermann, Theodor; Papadopoulos, Nikolaos G.; Finotto, Susetta (European Respiratory Journal, 2021)
Introduction: Interferon (IFN) responses have been reported to be defective in rhinovirus (RV)-induced asthma. The heterodimeric receptor of type I IFN (IFN-α/β) is composed of IFN-αR1 and IFN-αR2. Ligand binding to the IFN-α/β receptor complex activates signal transducer and activator of transcription (STAT) proteins STAT1 and STAT2 intracellularly. Although type III IFN (IFN-λ) binds to a different receptor containing IFN-λR1 and interleukin-10R2, its triggering leads to activation of the same downstream transcription factors. Here, we analysed the effects of RV on IFN type I and III receptors, and asked about possible Toll-like receptor 7/8 (TLR7/8) agonist R848-mediated IFN-αR1 and IFN-λR1 regulation. Methods: We measured IFN-α, IFN-β and IFN-λ and their receptor levels in peripheral blood mononuclear cell (PBMC) supernatants and cell pellets stimulated with RV1b and R848 in two cohorts of children with and without asthma recruited at pre-school age (PreDicta) and at primary school age (AGENDAS) as well as in cell supernatants from total lung cells isolated from mice. Results: We observed that R848 induced IFN-λR mRNA expression in PBMCs of healthy and asthmatic children, but suppressed IFN-αR mRNA levels. In murine lung cells, RV1b alone and together with R848 suppressed IFN-αR protein in T-cells compared with controls and in total lung IFN-λR mRNA compared with RV1b infection alone. Conclusions: In PBMCs from pre-school age children, IFN-αR mRNA was reduced and IFN-λR1 mRNA was induced upon treatment with the TLR7/8 agonist R848, thus suggesting new avenues for induction of antiviral immune responses in paediatric asthma.
CRIS-Team Scopus Importer:2021-06-04

Type 1 interferon alpha (IFN-a) regulation by respiratory viruses in pediatric asthma - Finotto, Susetta; Bergauer, Annika; Sopel, Nina; Kross, B.; Vuorinen, T.; Weiss, S. T.; Rauh, Manfred; Melichar, V. O.; Kiefer, Alexander; Zimmermann, Theodor; Ml, Kowalski; Jartti, T.; et al. (2017)
EVALuna2:33022

Vitamin D3 resolved human and experimental asthma via B lymphocyte-induced maturation protein 1 in T cells and innate lymphoid cells. - Grund, Janina; Krammer, Susanne; Yang, Zuqin; Mitländer, Hannah; Rauh, Manfred; Zirlik, Sabine; Kiefer, Alexander; Zimmermann, Theodor; Rieker, Ralf; Geppert, Carol-Immanuel; Papadopoulos, Nikolaos G.; Neurath-Finotto, Susetta (Journal of Allergy and Clinical Immunology: Global, 2023)
BACKGROUND: Vitamin D3 (VitD3) is known to have immunomodulatory functions, and VitD3 deficiency is associated with more severe asthma. OBJECTIVE: We aimed to assess the immunoregulatory effects of VitD3 food supplementation on asthma manifestation, with particular focus on T cells and type 2 innate lymphoid cells. METHODS: Preschool children and adult asthmatic cohorts were analyzed in the context of VitD3 supplementation and serum levels. In a murine model of ovalbumin-induced asthma, effects of diet VitD3 sufficiency and deficiency on T cells and type 2 innate lymphoid cells immune mechanisms were investigated. RESULTS: We found less severe and better-controlled asthma phenotypes along with reduced need for steroid medication in preschool children and asthmatic adults with VitD3 supplementation. VitD3 serum levels correlated with B lymphocyte-induced maturation protein 1 (Blimp-1) expression in blood peripheral mononuclear cells. VitD3-supplement-fed mice showed decreased asthmatic traits, with a decrease in IgE serum levels, reduced airway mucus, and increased IL-10 production by lung cells. Furthermore, we discovered an upregulation of effector T cells and Blimp-1+ lung tissue-resident memory T cells as well as induction of anti-inflammatory Blimp-1+ lung innate lymphoid cells producing IL-10. CONCLUSION: Supplementing VitD3 resulted in amelioration of clinical asthma manifestations in human studies as well as in experimental allergic asthma, indicating that VitD3 shifts proinflammatory immune responses to anti-inflammatory immune responses via upregulating Blimp-1 in lung innate lymphoid cells and tissue-resident memory cells.
EVALuna2:544627
Keywords: Allergic asthma; pediatric asthma; adult asthma; vitamin D3; vitamin D3 supplementation; TRM; ILC2s; Blimp-1; resolution of asthma